La representación simbólica del salvaje - González, José Manuel; Peraza, Xiomara; Guzmán, Nataly (ECA: Estudios Centroamericanos, 2004)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 59, No. 671, 2004: 958-963.